Beast Boy loves Raven - Garcia, Kami; Picolo, Gabriel; Haynes, Rob; Calderon, David; Downie, Gabriela (Burbank, CA, 2022)
While Raven Roth is finding a way to get rid of her demon father Trigon, Garfield Logan is understanding his newly found shapeshifting ability, and when their paths cross in Nashville they both feel a strong connection to one another.
Keywords: Fiction; (Fictitious character); Beast Boy; Fiction; (Fictitious character); (Fictitious character); Comic books, strips, etc; Raven; Raven; Beast Boy; Comic books, strips, etc; (Fictitious character); Fiction; Secrets; Fiction; Love; Fiction; Ability; Fiction; Cartoons and comics; Comic books, strips, etc; Secrecy; Comic books, strips, etc; Love; Comic books, strips, etc; Ability; Comic books, strips, etc; Superheroes; Superheroes; Fiction; Comic books, strips, etc; Nashville (Tenn.); Nashville (Tenn.); Comics (Graphic works); Graphic novels; Superhero comics; Romance comics